Cyber Terrorism Criminal Acts in the Perspective of Transnational Organized Crime - Okti Putri Andini (Unnes Law Journal, 2021)
This research was conducted to explain the legal instrument governing Cyber terrorism from an organized transnational crime perspective as well as analyzing the modus operandi used by Cyber terrorism. This research is a normative legal research using a qualitative approach to finding data sources by studying all the laws and regulations concerned with Cyber terrorism. Because this research is a normative legal research then the data sources used in this research are secondary data sources. In collecting data, authors conduct literature studies and the validity of the obtained data is examined using triangulation techniques. Then the results are analyzed and presented using a descriptive analytical method. The results of this study found that there were several international conventions that could be used as legal instruments for Cyber terrorism. And based on the study by the authors modus operandi used by terrorists in committing Cyber terrorism very diverse namely through: hacking, propaganda, fraud, DDoS attacks and the spread of viruses, worms or malware. The outcome of the results are: although there is no legal instrument that governs Cyber terrorism but some of the relevant and existing international conventions can be used as Cyber terrorism law resource, and it can be noted that there are various of modus operandi used by terrorists in Cyber terrorism.